The Welfare of Children. - Lindsey, Duncan (Oxford University Press, 2003)
According to the United Nations' latest data, the United States has more children living in poverty than any other industrialized nation in the world. More than a fifth of all children grow up in poverty. The poverty rates for African-American and Latino children often exceeds 40 percent. Furthermore, the United States--a country that once pioneered strategies to prevent child abuse and that now spends more money fighting child abuse than any other industrialized country--also has the highest rate of child abuse in the industrialized world. Against this background, Duncan Lindsey, a leading au.